2014
DOI: 10.1108/lm-06-2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Keeping ahead of the curve

Abstract: Purpose – This paper aims to present the results of a qualitative study of the continuing professional development (CPD) activities of academic librarians in Ireland. The benefits of CPD, the methods and strategies of engagement, and the role played by professional organisations are examined, with particular emphasis on the attitudes of librarians towards CPD. Design/methodology/approach – In total, 25 academic librarians were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Not only did they observe an organizational separation between "community" and technical functions, but they also noticed that specialized technical knowledge of software platforms and technical standards was becoming more critical for staff. In more recent years, analyses of digitally-connected library job advertisements have supported this finding: database design, metadata, systems administration expertise, familiarity with born digital materials, and web application development skills have become commonly sought (Tzoc and Millard 2011;Skene 2018), despite the fact that staff performing public services or liaison roles do not feel that these skills should be required for their work (Wilson and Halpin 2006;Corcoran and McGuinness 2014). In some cases, the desire to avoid skills silos results in the creation of "the unicorn job ad" (Schmidt 2018, 13), where an impossibly broad range of required skills are listed and positions are filled using a "best fit" model.…”
Section: Digital Knowledge and Skillsmentioning
confidence: 99%
“…Not only did they observe an organizational separation between "community" and technical functions, but they also noticed that specialized technical knowledge of software platforms and technical standards was becoming more critical for staff. In more recent years, analyses of digitally-connected library job advertisements have supported this finding: database design, metadata, systems administration expertise, familiarity with born digital materials, and web application development skills have become commonly sought (Tzoc and Millard 2011;Skene 2018), despite the fact that staff performing public services or liaison roles do not feel that these skills should be required for their work (Wilson and Halpin 2006;Corcoran and McGuinness 2014). In some cases, the desire to avoid skills silos results in the creation of "the unicorn job ad" (Schmidt 2018, 13), where an impossibly broad range of required skills are listed and positions are filled using a "best fit" model.…”
Section: Digital Knowledge and Skillsmentioning
confidence: 99%
“…Focusing on barriers that prevent librarians from attending conferences, research by Adomi, Alakpodia, and Akporhonor (2006), Corcoran and McGuinness (2014), Eke (2011), the Australian Library and Information Association (ALIA, 2014a), Schmehl Hines (2014) and Terrill (2014) indicated that lack of funding was the most significant element inhibiting conference attendance. Time constraints were found to be another barrier by researchers such as Schmehl Hines (2014), ALIA (2014a), and Corcoran and McGuinness (2014). Adomi et al (2006) and Eke (2011) also identified lack of awareness of an event preventing library staff from attending conferences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Electronic mailing lists (also known as listservs) are mentioned in the LIS literature as commonly used sources of information 9 [4,28,6,20]. In Krasulski's 2014 survey of access services librarians, 67 percent stated that they used electronic mailing lists to keep current [20].…”
Section: Social Media and Electronic Mailing Listsmentioning
confidence: 99%
“…Conferences are particularly favored as learning opportunities among information systems academics [9] and librarians [4,15,6,20,25]. Tomaszewski and MacDonald [33] suggested subject-specific conferences as valuable professional development opportunities for academic librarians with subject responsibilities.…”
Section: Conferencesmentioning
confidence: 99%
See 1 more Smart Citation